MTSET modification of D4S6 cysteines stabilize the fast inactivated state of Nav1.5 sodium channels - O’Leary, Michael E.; Chahine, Mohamed (Frontiers in Pharmacology, 2015)
The transmembrane S6 segments of Na+ sodium channels form the cytoplasmic entrance of the channel and line the internal aspects of the aqueous pore. This region of the channel has been implicated in Na+ channel permeation, gating and pharmacology. In this study we utilized cysteine substitutions and methanethiosulfonate reagent (MTSET) to investigate the role of the S6 segment of homologous domain 4 (D4S6) in the gating of the cardiac (Nav1.5) channel. D4S6 cysteine mutants were heterologously expressed in tsA201 cells and currents recorded using whole-cell patch clamp. Internal MTSET reduced the peak Na+ currents, induced hyperpolarizing shifts in steady-state inactivation and slowed the recovery of mutant channels with cysteines inserted near the middle (F1760C, V1763C) and C-terminus (Y1767C) of the D4S6. These findings suggested a link between the MTSET inhibition and fast inactivation. This was confirmed by expressing the V1763C and Y1767C mutations in non-inactivating Nav1.5 channels. Removing inactivation abolished the MTSET inhibition of the V1763C and Y1767C mutants. The data indicate that the MTSET-induced reduction in current primarily results from slower recovery from inactivation that produces hyperpolarizing shifts in fast inactivation and decreases the steady-state availability of the channels. This contrasted with a cysteine inserted near the C-terminus of the D4S6 (I1770C) where MTSET increased the persistent Na+ current at depolarized voltages consistent with impaired fast inactivation. Covalent modification of D4S6 cysteines with MTSET adduct appears to reduce the mobility of the D4S6 segment and stabilize the channels in the fast inactivated state. These findings indicate that residues located near the middle and C-terminus of the D4S6 play an important role in fast inactivation.